Energycopia : Energy Conservation - Diwan, Parag (New Delhi : Pentagon energy press, 2008)
No other resource has been so critical in shaping destiny of nations, the development of military and global trade strategies and relationships among countries. No other resource has offered such great promises for improving the well being of entire nations
Vol I
includes bibliography and index.
Keywords: Energycopia; Power resources; Power resources -- India